Concomitant Extramedullary Plasmacytoma in the Oropharynx and Hypopharyngeal Squamous Cell Carcinoma - Hiroki Sato; Shoko Yoshimasu; Isaku Okamoto; Akira Shimizu; Yasuaki Katsube; Hideki Tanaka; Kiyoaki Tsukahara (Case Reports in Otolaryngology)
We report a rare case of hypopharyngeal squamous cell carcinoma occurring synchronously with extramedullary plasmacytoma (EPM) of the oropharynx in which radiotherapy was used as the curative treatment. A 73-year-old man presented with a sore throat that had persisted for 6 months. Examination revealed a superficial, smooth tumorous lesion at the base of his tongue with a red hue in the oropharynx. In addition, a protruding tumor was observed on the mucosal surface in the right piriform recess of the hypopharynx, and computed tomography revealed thickening of the pharyngeal wall at the right tongue base and in the right piriform recess of the hypopharynx. Because no definitive diagnosis could be reached for the lesion at the base of the tongue, the entire tongue-base tumor was resected by transoral surgery under endoscopy. Proliferation of plasma cells in the tumor was detected, and a bone marrow puncture test ruled out multiple myeloma leading to a definitive diagnosis of Stage I (cT1N0M0) squamous cell carcinoma in the right piriform recess of the hypopharynx and primary extramedullary plasmacytoma in the oropharynx. Radiotherapy was selected for curative treatment with a complete response for both cancers. No recurrences have been observed as of 12 months postoperatively.